2016
DOI: 10.1017/s0022215116008112
|View full text |Cite
|
Sign up to set email alerts
|

Role of atopy in chronic rhinosinusitis with nasal polyps: does an atopic condition affect the severity and recurrence of disease?

Abstract: There was no association between atopy status and either disease severity or recurrence in patients with chronic rhinosinusitis with nasal polyps, although atopic patients were younger than non-atopic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
2
11
1
Order By: Relevance
“…Therefore, we can conclude that eosinophils may trigger a more severe form of inflammation in the context of CRSwNP compared to the noneosinophilic inflammatory cells. However, our results showed no significant difference between the ECRSwNP and nECRSwNP groups with respect to the SNOT-20 score, VAS score, endoscopy score, or CT score ( p > 0.05); these findings are consistent with the results of a recently published paper that compared the clinical markers of CRS with disease severity [21,22,23]. …”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we can conclude that eosinophils may trigger a more severe form of inflammation in the context of CRSwNP compared to the noneosinophilic inflammatory cells. However, our results showed no significant difference between the ECRSwNP and nECRSwNP groups with respect to the SNOT-20 score, VAS score, endoscopy score, or CT score ( p > 0.05); these findings are consistent with the results of a recently published paper that compared the clinical markers of CRS with disease severity [21,22,23]. …”
Section: Discussionsupporting
confidence: 92%
“…In investigating the role of allergy in CRS patients, Li et al 11 found 47% of their patients had allergy but the disease severity and recurrence rates were the same, irrespective of the allergy status. When the presence of allergy was related to the findings of CTPNS, Erbek et al 12 and Peric et al 13 found no association between allergy with both endoscopic findings and LM scores in their respective studies.…”
Section: Discussionmentioning
confidence: 99%
“…The Lund‐Mackay CT score was found to be similar between the allergen‐sensitized and nonatopic patients among our CRS population (Table ). Other studies also did not find a statistically significant association between atopy status and CRS or differences in the Lund‐Mackay CT score between the atopic and nonatopic group . The Lund‐McKay score does not differentiate diseased sinuses between 5% opacified sinus and 95% opacified sinus, and does not differentiate location of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also did not find a statistically significant association between atopy status and CRS or differences in the Lund-Mackay CT score between the atopic and nonatopic group. 16,17 The Lund-McKay score does not differentiate diseased sinuses between 5% opacified sinus and 95% opacified sinus, and does not differentiate location of disease. It is not surprising that an absolute Lund-Mackay score did not differentiate these groups.…”
Section: Discussionmentioning
confidence: 99%